Simplify −34r + 3 − 56r − 6

1 answer

To simplify the expression, combine like terms. Like terms are terms that contain the same variables raised to the same power. Here, the like terms are −34r and −56r, which are both coefficients of r, and the constants 3 and −6.

First, simplify the r terms by adding them together:
−34r + (−56r) = −34r − 56r = −90r

Next, combine the constant terms:
3 + (−6) = 3 − 6 = −3

Now that you have combined the like terms, the simplified expression is:
−90r − 3

That's the simplified form of the original expression.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions